In vitro and in vivo evaluation of chitosan buccal films of ondansetron hydrochloride - Koland, Marina; Charyulu, R Narayana; K, Vijayanarayana; Prabhu, Prabhakara (International Journal of Pharmaceutical Investigation)
Buccal films of ondanstron hydrochloride were fabricated from mucoadhesive polymer, chitosan, and polyvinyl pyrrolidone (PVP K30) for the purpose of prolonging drug release and improving its bioavailability. All fabricated film formulations prepared were smooth and translucent, with good flexibility. The weight and thickness of all the formulations were found to be uniform. Drug content in the films ranged from 98 ; 99%, indicating favorable drug loading and uniformity. The inclusion of PVP K30, a hydrophilic polymer, significantly reduced the bioadhesive strength and in vitro mucoadhesion time of the films, although the degree of swelling increased. In vitro drug release studies in simulated saliva showed a prolonged release of over five to six hours for all formulations, except C4, with 99.98% release in 1.5 hours. Kinetic analysis of the release data indicated that the best fit model with the highest correlation coefficient for all formulations was the Peppas model. In vivo studies, on selected films in rabbits, were conducted, to determine the pharmacokinetic parameters such as Cmax, Tmax, and AUC0, using model-independent methods with nonlinear least-squares regression analysis. The AUC and values of Cmax of ondansetron hydrochloride were found to be significantly greater (P ; 0.005) than the selected films C2 and C3, as compared to those from the oral solution, thereby confirming improved bioavailability via the buccal route. The Tmax values were also significantly greater (P ; 0.005), indicating the slower release of the drug from buccal films, thereby, providing prolonged effects. Good in vitro;in vivo correlation was observed with R2 values exceeding 0.98, when the percentage of drug released was correlated with the percentage of drug absorbed.
Keywords: Buccal; chitosan; mucoadhesive; ondansetron; polyvinyl pyrrolidone